The Associations of cerebral blood flow and white matter hyperintensities with tau and amyloid-beta across the Alzheimer’s disease spectrum - Keshuo Lin; Perminder S. Sachdev; Jiyang Jiang (Brain Imaging and Behavior, 2026)
Although the associations between cerebrovascular dysfunctions and Alzheimer’s disease are increasingly appreciated, the relationship of cerebral blood flow and white matter hyperintensities with tau and amyloid-β pathology remains unclear, particularly in the longitudinal context. This study investigated cross-sectional and longitudinal associations of cerebral blood flow and white matter hyperintensities with tau and amyloid-β pathology using multimodal imaging and blood biomarkers in 179 participants from the ADNI3 cohort. Participants underwent structural (T1-weighted, T2-weighted FLAIR) and arterial spin labelling perfusion MRI, tau and amyloid-β PET, and plasma assay tests for amyloid-β 42, amyloid-β 40, and phosphorylated tau-217. Tau from PET was negatively associated with cerebral blood flow both cross-sectionally and longitudinally in the posterior brain, independent of amyloid-β quantified from PET. Higher white matter hyperintensities volumes were associated with higher levels of tau and amyloid-β at baseline, but the associations were significantly attenuated after further adjusting for amyloid-β and tau, respectively. Plasma amyloid-β 42/40 ratio was negatively associated with white matter hyperintensity volumes both cross-sectionally and longitudinally. In conclusion, tau pathology showed spatially specific associations with cerebral hypoperfusion, independent of amyloid-β, particularly in posterior regions. The attenuation of associations of white matter hyperintensities with amyloid-β and tau after adjustment may reflect shared disease-related variance rather than distinct independent effects.

Retraction Note: Mapping NAD+ metabolism in the brain of ageing Wistar rats: potential targets for influencing brain senescence - Nady Braidy; Anne Poljak; Ross Grant; Tharusha Jayasena; Hussein Mansour; Tailoi Chan-Ling; Gilles J. Guillemin; George Smythe; Perminder Sachdev (Biogerontology, 2026)

Do associations of neighbourhood attributes with cognitive function vary by socio-economic status? A 12-year follow-up study of older Australians - Ester Cerin; Maria V. Soloveva; Miguel A. Molina; Ralf-Dieter Schroers; Yu-Tzu Wu; Perminder S. Sachdev; Luke D. Knibbs; Nicolas Cherbuin; Bin Jalaludin; Suzanne Mavoa; Kaarin J. Anstey (Science of The Total Environment, 2025)

Exploring the link between brain topological resilience and cognitive performance in the context of aging and vascular risk factors: A cross-ethnicity population-based study - Hao Liu; Jing Jing; Jiyang Jiang; Wei Wen; Wanlin Zhu; Zixiao Li; Yuesong Pan; Xueli Cai; Chang Liu; Yijun Zhou; Xia Meng; Yilong Wang; et al. (Science Bulletin, 2024)

A systematic review of diet and medication use among centenarians and near-centenarians worldwide - Zhaoli Dai; Sue Yi Lee; Srishti Sharma; Shahid Ullah; Edwin C. K. Tan; Henry Brodaty; Aletta E. Schutte; Perminder S. Sachdev (GeroScience, 2024)
Centenarians represent a phenomenon of successful aging. This systematic review aimed to understand lifestyles and health practices, focusing on diet and medication use for healthy longevity in community-based adults 95 years or over. Medline, CINAHL, Scopus, and gray literature were searched from 1 January 2000 to 10 December 2022. Study quality was assessed using the Modified Newcastle-Ottawa Scale (mNOS). Pooled prevalence [%; 95% confidence interval] for categorical variables and pooled mean for continuous variables were estimated for demographics, weight status, lifestyle factors, medications, and health conditions. Of 3392 records screened, 34 studies were included in the review, and 71% (24/34) met the 6/8 criteria in mNOS. Centenarians/near-centenarians’ ages ranged from 95 to 118 years, with 75% (71–78%) female and 78% (68–88%) living in rural areas. They had an overall healthy lifestyle: current smoking (7%; 5–9%), drinking (23%; 17–30%), normal weight (52%; 42–61%), overweight (14%; 8–20%), physical activity (23%; 20–26%), and sleep satisfaction (68%; 65–72%). Diet averaged 59.6% carbohydrate, 18.5% protein, and 29.3% fat; over 60% consumed a diverse diet, and < 20% preferred salty food, contributing to lower mortality risks and functional decline. About half used antihypertensives (49%; 14–84%) or other cardiovascular drugs (48%; 24–71%), with an average of 4.6 medications. Common health issues included impaired basic activities of daily living (54%; 33–74%), hypertension (43%; 21–65%), and dementia (41%; 23–59%). The findings of this systemic review underscore the pivotal role of dietary practice and weight management in healthcare strategies to promote healthy ageing. It also recognises rural living styles and sleep hygiene as potential factors contributing to healthy longevity.

Brain structural covariances in the ageing brain in the UK Biobank - Chao Dong; Anbupalam Thalamuthu; Jiyang Jiang; Karen A. Mather; Perminder S. Sachdev; Wei Wen (Brain Structure and Function, 2024)
The morphologic properties of brain regions co-vary or correlate with each other. Here we investigated the structural covariances of cortical thickness and subcortical volumes in the ageing brain, along with their associations with age and cognition, using cross-sectional data from the UK Biobank ( N = 42,075, aged 45–83 years, 53% female). As the structural covariance should be estimated in a group of participants, all participants were divided into 84 non-overlapping, equal-sized age groups ranging from the youngest to the oldest. We examined 84 cortical thickness covariances and subcortical covariances. Our findings include: (1) there were significant differences in the variability of structural covariance in the ageing process, including an increased variance, and a decreased entropy. (2) significant enrichment in pairwise correlations between brain regions within the occipital lobe was observed in all age groups; (3) structural covariance in older age, especially after the age of around 64, was significantly different from that in the youngest group (median age 48 years); (4) sixty-two of the total 528 pairs of cortical thickness correlations and 10 of the total 21 pairs of subcortical volume correlations showed significant associations with age. These trends varied, with some correlations strengthening, some weakening, and some reversing in direction with advancing age. Additionally, as ageing was associated with cognitive decline, most of the correlations with cognition displayed an opposite trend compared to age associated patterns of correlations.

Retraction Note to: Changes in Cathepsin D and Beclin-1 mRNA and protein expression by the excitotoxin quinolinic acid in human astrocytes and neurons - Nady Braidy; Bruce J. Brew; Nibaldo C. Inestrosa; Roger Chung; Perminder Sachdev; Gilles J. Guillemin (Metabolic Brain Disease, 2023)

Hormonal factors moderate the associations between vascular risk factors and white matter hyperintensities - Abdullah Alqarni; Wei Wen; Ben C. P. Lam; John D. Crawford; Perminder S. Sachdev; Jiyang Jiang (Brain Imaging and Behavior, 2023)

High polygenic risk score for exceptional longevity is associated with a healthy metabolic profile - Mary Revelas; Anbupalam Thalamuthu; Anna Zettergren; Christopher Oldmeadow; Jenna Najar; Nazib M. Seidu; Nicola J. Armstrong; Carlos Riveros; John B. Kwok; Peter R. Schofield; Julian N. Trollor; Margda Waern; et al. (GeroScience, 2023)
Healthy metabolic measures in humans are associated with longevity. Dysregulation leads to metabolic syndrome (MetS) and negative health outcomes. Recent exceptional longevity (EL) genome wide association studies have facilitated estimation of an individual’s polygenic risk score (PRS) for EL. We tested the hypothesis that individuals with high ELPRS have a low prevalence of MetS. Participants were from five cohorts of middle-aged to older adults. The primary analyses were performed in the UK Biobank (UKBB) ( n = 407,800, 40–69 years). Replication analyses were undertaken using three Australian studies: Hunter Community Study ( n = 2122, 55–85 years), Older Australian Twins Study ( n = 539, 65–90 years) and Sydney Memory and Ageing Study ( n = 925, 70–90 years), as well as the Swedish Gothenburg H70 Birth Cohort Studies ( n = 2273, 70–93 years). MetS was defined using established criteria. Regressions and meta-analyses were performed with the ELPRS and MetS and its components. Generally, MetS prevalence (22–30%) was higher in the older cohorts. In the UKBB, high EL polygenic risk was associated with lower MetS prevalence (OR = 0.94, p = 1.84 × 10 –42 ) and its components ( p < 2.30 × 10 – 8 ). Meta-analyses of the replication cohorts showed nominal associations with MetS ( p = 0.028) and 3 MetS components ( p < 0.05). This work suggests individuals with a high polygenic risk for EL have a healthy metabolic profile promoting longevity.

Cognitive decline is associated with frequency-specific resting state functional changes in normal aging - Dongqiong Fan; Tao Liu; Jiyang Jiang; Nicole A. Kochan; Yilong Wang; Henry Brodaty; Perminder S. Sachdev; Wei Wen (Brain Imaging and Behavior, 2022)

The relationship of cerebral microbleeds to cognition and incident dementia in non-demented older individuals - Matt Paradise; Adam Seruga; John D. Crawford; Joga Chaganti; Anbupalam Thalamuthu; Nicole A. Kochan; Henry Brodaty; Wei Wen; Perminder S. Sachdev (Brain Imaging and Behavior, 2019)

Validated Alzheimer’s Disease Risk Index (ANU-ADRI) is associated with smaller volumes in the default mode network in the early 60s - Nicolas Cherbuin; Marnie E. Shaw; Erin Walsh; Perminder Sachdev; Kaarin J. Anstey (Brain Imaging and Behavior, 2019)

The relationship between voxel-based metrics of resting state functional connectivity and cognitive performance in cognitively healthy elderly adults - Haobo Zhang; Perminder S. Sachdev; Anbupalam Thalamuthu; Yong He; Mingrui Xia; Nicole A. Kochan; John D. Crawford; Julian N. Trollor; Henry Brodaty; Wei Wen (Brain Imaging and Behavior, 2018)

Deep white matter hyperintensities, microstructural integrity and dual task walking in older people - Tabassom Ghanavati; Myriam Sillevis Smitt; Stephen R. Lord; Perminder Sachdev; Wei Wen; Nicole A. Kochan; Henry Brodaty; Kim Delbaere (Brain Imaging and Behavior, 2018)

Incidental findings on cerebral MRI in twins: the Older Australian Twins Study - Rebecca Koncz; Adith Mohan; Laughlin Dawes; Anbupalam Thalamuthu; Margaret Wright; David Ames; Teresa Lee; Julian Trollor; Wei Wen; Perminder Sachdev (Brain Imaging and Behavior, 2018)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Higher Fasting Plasma Glucose is Associated with Increased Cortical Thinning Over 12 Years: The PATH Through Life Study - Marnie E. Shaw; Julia Nettersheim; Perminder S. Sachdev; Kaarin J. Anstey; Nicolas Cherbuin (Brain Topography, 2017)

Cortical Thinning at Midlife: The PATH Through Life Study - Marnie E. Shaw; Walter P. Abhayaratna; Perminder S. Sachdev; Kaarin J. Anstey; Nicolas Cherbuin (Brain Topography, 2016)

RETRACTED ARTICLE: Changes in Cathepsin D and Beclin-1 mRNA and protein expression by the excitotoxin quinolinic acid in human astrocytes and neurons - Nady Braidy; Bruce J. Brew; Nibaldo C. Inestrosa; Roger Chung; Perminder Sachdev; Gilles J. Guillemin (Metabolic Brain Disease, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

RETRACTED ARTICLE: Mapping NAD+ metabolism in the brain of ageing Wistar rats: potential targets for influencing brain senescence - Nady Braidy; Anne Poljak; Ross Grant; Tharusha Jayasena; Hussein Mansour; Tailoi Chan-Ling; Gilles J. Guillemin; George Smythe; Perminder Sachdev (Biogerontology, 2014)

Alpha-Synuclein Transmission and Mitochondrial Toxicity in Primary Human Foetal Enteric Neurons In Vitro - Nady Braidy; Wei-Ping Gai; Ying Hua Xu; Perminder Sachdev; Gilles J. Guillemin; Xing-Mai Jiang; J. William O. Ballard; Martin P. Horan; Zhi Ming Fang; Beng H. Chong; Daniel Kam Yin Chan (Neurotoxicity Research, 2014)